Formação inicial do profissional da pedagogia na região sudoeste do Paraná - Crestani, Solange Natalina Boesing (2018)
This dissertation discusses the initial formation of the pedagogy professional in the Southwest region of Paraná. The objective of the research was to analyze how this training process occurs, specifically to identify the Pedagogy courses of the referred region, as well as to verify and describe the theoretical presuppositions present in the pedagogical projects of the Pedagogy courses, to analyze the professional conception present in the pedagogical projects and finally to analyze the curricular matrices of the courses to verify if they are in line with the National Curriculum Guidelines for Teacher Training (2015). The justification of this research is directed to the analysis of the initial formation process of the pedagogue, the multidimensionality and specificity of the performance of this professional, the complexity of this training process and its social dimension. This is an exploratory and qualitative research. In order to answer, our inquiries, we opted to analyze the pedagogical projects of course and the curricular matrices of the public institutions that make the course available in the face-to-face modality of the Southwest region of Paraná, through the method of content analysis proposed by Bardin (2016). In this way, the main considerations show that the theoretical assumptions of the researched institutions lead to the understanding that they are adherents of the historical-critical pedagogy of Demerval Saviani, so they point out that education must relate dialectically with society, to understand education one must understand human nature. Thus, these institutions recognize the process of teacher training as a social and cultural action, which must intervene in reality. To the one that conceives the conception of professional that is intended to form, the institutions point out that the egress of the course of pedagogy must present consistent theoretical and practical formation. So that he knows how to respect the diversity found in the educational and social spheres. To do so, it must be a teacher-researcher, who seeks to research his practice and improve it. It is also evident that the institutions present curricular matrices, which are in line with the National Curriculum Guidelines for Teacher Education (2015). The contribution of this dissertation is to encourage critical reflection on the process of initial training of professionals in pedagogy in the Southwest region of Paraná and to collaborate in reflexive processes related to university management. Thus, such knowledge can be used in the construction of concepts pertinent to the process of initial formation of pedagogues and pedagogues, contributing to the improvement of courses offered in the southwestern region of Paraná.